Formulation of the Balm Aromatherapy Combination Using the Essential Oils Ocimum basilicum L. and Cymbopogon citratus DC - Cahyaningrum, Putu Lakustini; Suta, Ida Bagus Putra; Sudiartawan, I Putu; Saraswati, Ida Ayu Asri Diva; Dirgayasa, Pande Nyoman Selamet (Journal of Tropical Pharmacy and Chemistry, 2024)
This study aimed to analyze the formulation of an aromatherapy balm composed of the essential oils O. basilicum L. and C. citratus DC. Experimental research design involving the compilation of five balm formulations at concentrations of 0, 5, 10, 15, and 20%. For four months, balm formulations were made, and physical, chemical, and microbiological tests were carried out, which were further analyzed descriptively. The findings showed that the yield of essential oils obtained from distillation reached 0.19% w/v (O. basilicum L.) and 0.24% w/v (C. citratus DC). All formulations at concentrations of 0, 5, 10, 15, and 20% passed the organoleptic tests for topical dosage balms. This means that they were semisolid, smelled like essential oils, and were yellowish-brown based on the raw materials. The balm is completely homogeneous; there are no granules, and the color is evenly spread throughout the smear. The pH for the topical preparations ranged from 6–7, the dispersion power ranged from 5.02–6.10, and the adhesion ratio ranged from 2–6 depending on the concentration. Microbiological testing revealed that the aromatherapy balm was free of S. aureus and P. aeruginosa bacteria.